De novo MECP2 duplication in two females with random X-inactivation and moderate mental retardation - Grasshoff, Ute; Bonin, Michael; Goehring, Ina; Ekici, Arif; Dufke, Andreas; Cremer, Kirsten; Wagner, Nicholas; Rossier, Eva; Jauch, Anna; Walter, Michael; Bauer, Claudia; Bauer, Peter; et al. (European journal of human genetics, 2011)
Xq28 duplications including MECP2 are a well-known cause of severe mental retardation in males with seizures, muscular hypotonia, progressive spasticity, poor speech and recurrent infections that often lead to early death. Female carriers usually show a normal intellectual performance due to skewed X-inactivation (XCI). We report on two female patients with a de novo MECP2 duplication associated with moderate mental retardation. In both patients, the de novo duplication occurred on the paternal allele, and both patients show a random XCI, which can be assumed as the triggering factor for the phenotype. Furthermore, we describe the phenotype that might be restricted to unspecific mild-to -moderate mental retardation with neurological features in early adulthood.
Gesehen am 11.07.2022